IDAROTU BARAMIJ AL-LUGHAH AL-’ARABIYAH FI QISMI AL-LUGHAH LADA AL-THOLABAT BIMA’HAD DARUL AMAN - Qur'ani, Ainun Suci; Mufidah, Nuril; Amrullah, Abdul Malik Karim; Maulidi (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
This study describes the management of Arabic language programs in the language department for ‎female students at Darul Aman Institute. This research aimed to know the planning and objectives ‎of the management of Arabic language programs by the Language Department for female students ‎at Darul Aman Institute, and to know how to organize the management of Arabic language ‎programs for the Language Department for female students at Darul Aman Institute, the study ‎relied on the qualitative entrance research methodology and case study methodology, and data ‎collection through interview, field observation and document analysis. The researchers used data ‎analysis of Miles and Huberman. The result of this research is that the planning and objectives of the ‎Arabic language programs in the language department for female students at Darul Aman Institute ‎include: setting the schedule for speaking Arabic to develop students' discipline in speaking Arabic, ‎conducting a language competition to expand the students' culture and to develop the language ‎skills of students by establishing a linguistic quarantine, and producing a vocabulary dictionary and ‎language conversation in order to dispense with students' vocabulary and memorize it and then test ‎it at the end of the month to assess the development of their language level, upgrading students' ‎language skills by doing additional study To teach those who have a poor level of language and the ‎establishment of a language court, and the last plan is to find ways to develop students' language ‎skills by making vocabulary boards and conversation and by preparing to watch linguistic films and ‎linguistic songs. How to organize its administration is the organizational structure of the staff, the ‎installation of student organizations from the language department, as well as the creation and ‎establishment of a language violation court‏.‏